Tell me why I don't like Mondays: investigating day of the week effects on job satisfaction and psychological well-being - Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2002)
This work explores the relationships between day and month of interview and self-reported job satisfaction and mental health scores. The analysis uses data on individuals from the first 9 waves of the BHPS. Evidence presented here suggests that self-reported levels of job satisfaction and subjective mental health systematically vary according to the days of the week and month of the year in which respondents are interviewed. Results suggest that over-employment has the largest depressive effect on job satisfaction among workers in Britain, while a deteriorating financial situation has a large negative impact on mental well-being.
Keywords: 330